2009
DOI: 10.1002/jor.20925
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescence labeled mesenchymal stem cells in pluronic F127 and porous hydroxyapatite as a bone substitute for posterolateral spinal fusion

Abstract: Posterolateral spinal fusion is used to treat patients with degenerative spinal disorders. We investigated the effectiveness of a mesenchymal stem cell (MSC)/Pluronic F127/Interpore hybrid graft for spinal fusion in rabbits. Spinal fusion was examined using radiography, manual palpation, computed tomography (CT), torsional loading tests, and histological analysis. Using a PKH fluorescence labeling system, we also examined whether the newly formed bone was derived from the transplanted MSCs. We found that the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…The aim of this study was to achieve a fusion rate of less than 40 % and then determine whether autologous bone marrow augmented arthrodesis. Other studies subsequently used this bone paucity model to provide a larger potential for improved fusion rates with a variety of bone graft substitutes [13][14][15][16][17][18][19][20][21][22]. While our study found a significant positive relationship between volume of autograft and fusion rates, a tenfold range of volume of autograft (1.4-12 cm 3 ) was used in the studies evaluated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The aim of this study was to achieve a fusion rate of less than 40 % and then determine whether autologous bone marrow augmented arthrodesis. Other studies subsequently used this bone paucity model to provide a larger potential for improved fusion rates with a variety of bone graft substitutes [13][14][15][16][17][18][19][20][21][22]. While our study found a significant positive relationship between volume of autograft and fusion rates, a tenfold range of volume of autograft (1.4-12 cm 3 ) was used in the studies evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Chen et al [15] argued that the higher fusion rate seen in the younger rabbits utilized in their study might be attributed to a more vigorous healing response relative to older rabbits used in previous studies. Indeed, younger rabbits may have a higher capacity for spinal fusion since their skeletal systems are relatively immature, and ongoing bone remodeling could accelerate fusion.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In essence, the goal is to expand MSCs on tissue culture plastic prior to loading of the cell population onto a scaffold in order to increase osteoprogenitor cell numbers and to hopefully improve the chances of a successful fusion. A number of small and large animal studies have compared the effects of using scaffolds seeded with culture-expanded MSCs in a variety of spinal fusion models, although the results have proved somewhat mixed (Table 3) [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The discrepancy in findings could, in part, be explained by differences in culture expansion techniques used in the various studies.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 95%
“…8 A critical variable in stem cell-based therapy is the number of cells used for implantation (10 7 - 10 8 ) in a suitable 3D graft, 8,9 but the treatment used by Eziker et al involved 10 6 MSCs/100 mL floating in a vehicle medium (sterile saline or PBS), without the presence of platelet-rich plasma, which has been shown to be able to regenerate functional bone in alveolar deficiencies. 10 We think that sound results are crucial in stem cell research and particularly important in order to avoid " dark stem cell therapy" in orthodontic patients.…”
mentioning
confidence: 99%